Solution Deposition of High-Quality AgBiS₂ Thin Films via a Binary Diamine-Dithiol Solvent System - Ghasemi, Mehri; He , Dongxu; Jia, Baohua; Wen, Xiaoming (Materials and Sustainability, 2025)
Article Solution Deposition of High-Quality AgBiS₂ Thin Films via a Binary Diamine-Dithiol Solvent System Mehri Ghasemi 1,2,*, Dongxu He 2, Baohua Jia 1,* and Xiaoming Wen 1,* 1 School of Science, RMIT University, Melbourne, VIC 3000, Australia 2 School of Chemical Engineering, University of Queensland, Brisbane, QLD 4072, Australia * Correspondence: mehri.ghasemi@rmit.edu.au Received: 18 February 2025; Revised: 8 April 2025; Accepted: 10 April 2025; Published: 21 April 2025 Abstract: Lead halide perovskites suffer from toxicity and instability challenges due to their sensitivity to various environmental factors, such as humidity, heat and prolonged light illumination. Developing stable and lead-free alternatives that can still be solution-processed has attracted significant research interests in the past years. Bismuth-based chalcogenide materials have emerged as one promising candidate. In particular, silver bismuth disulfide (AgBiS2) has garnered increasing interest due to its high absorption coefficient (105–103 cm−1 in the 400–1100 nm range) and a favourable bandgap of ~1.3 eV. However, the poor solubility of AgBiS2 precursors in the conventional solvents has hindered the solution fabrication of high-quality thin-films. While previous studies have explored deposition techniques such as spray pyrolysis, hot-injection synthesis with ligand exchange, and nanocrystal ink-based in situ passivation, these methods often involve complex ligand engineering, high processing costs, or challenges in achieving uniform and compact thin-film. In this work, we introduce a novel solution-based spin-coating approach for the deposition of high-quality, phase-pure AgBiS2 thin-films, overcoming the solubility limitations of conventional precursors. By employing a binary chelating solvent mixture of ethylenediamine and 1,2-ethanedithiol, we achieve bidentate coordination with metal cations, enabling the dissolution of Ag2S and Bi2S3 through a chelation-assisted mechanism. This facilitates the formation of compact and uniform films with precise roughness control. This method eliminates the need for high-temperature processing or vacuum-assisted crystallization, significantly enhancing scalability and cost-effectiveness. A planar heterojunction device architecture incorporating TiO2 as the electron transport layer (FTO/c-TiO2/AgBiS2/P3HT/Au) is demonstrated with the initial power conversion efficiency (PCE) of 0.62%, offering an effective charge extraction pathway. With further passivation and doping optimizations, this approach presents a new, scalable route for solution-processed AgBiS2 thin-films, providing a promising alternative to ligand-engineered nanocrystal-based methods with potential advantages in stability, reproducibility, and manufacturing compatibility.